A rational synthesis of ultrasmall palladium-based alloys with superhydrophilicity as biocompatible agents and recyclable catalysts. Issue 13 (11th March 2022) - Chen, Shiyue; He, Xiaoxiao; Yuan, Xulei; Wang, Zhenyu; Wang, Teng; He, Chengdian; Zhang, Ximu; Mao, Xiang
Abstract : As essential controlling parameters, the local surface area (size distribution) and polarity property of the surface molecules can determine the catalytic activity and biocompatibility directly. Abstract : As essential controlling parameters, the local surface area (size distribution) and polarity property of the surface molecules can determine the catalytic activity and biocompatibility directly. Here, ultrasmall palladium-based alloys (FePd, FePdCo, and FePdCu NCs) were developed to serve as artificial degradation catalysts with superhydrophilicity (SPh), biocompatibility, and reusability, which were referred to as "biocatalysts". As synthesized in aqueous solvent with negative surface potential while dispersing in water medium, because of the surface biological molecules effect. The obtained alloys illustrated a size distribution of about 3.5 nm. Additionally, owing to SPh property, these alloys could be stored in water up to 30 days without any precipitation and retained their monodisperse morphology in colloidal solutions. The cytotoxicity assessment of the alloys by exposing to L-929 cells over 3 days indicated that it maintained cell viability of >80% even up to 390 μg mL −1 (concentration of alloys). Furthermore, they exhibited an obvious enhancement in the catalytic performance for degrading Rhodamine B (RhB) and 4-nitrophenol (4-NP). The recyclable utilization of biocatalysts demonstrates durable stability even after 8 reduction cycles.